Improving Learning Outcomes in Fraction Addition Through the Concrete-Representational Abstract Method Based on Problem Based Learning in Elementary School Students' Learning Difficulties - Suratmi, Suratmi; Azizah, Nur (Journal of Innovation and Research in Primary Education, 2025)
Mathematics learning difficulties, particularly in fraction addition, represent a significant challenge in elementary education, with students experiencing low academic achievement and diminished self-confidence. This study aimed to improve fraction addition learning outcomes among elementary students with learning difficulties through the implementation of Concrete-Representational-Abstract (CRA) method based on Problem-Based Learning (PBL). A Classroom Action Research design following the Kemmis and McTaggart spiral model was conducted over two cycles with 20 fifth-grade students at an elementary school in Kaliorang District, East Kutai Regency. The study specifically focused on four students with learning difficulties as primary subjects. Data collection employed learning modules, observation sheets, worksheets, evaluation tests, and field notes. Qualitative analysis followed the Miles and Huberman framework, while quantitative analysis utilized percentage and average calculations. Success criteria required students to achieve a minimum average score of ≥75 with 80% class mastery. The intervention demonstrated exceptional effectiveness, with overall proficiency rates improving from 20% (pre-cycle) to 75% (Cycle I) to 100% (Cycle II). Among students with learning difficulties, proficiency increased from 0% to 100%, with average scores improving by 38.25 points. Class average scores rose from 65.70 to 89.80. Student engagement increased by 25.41%, while teacher performance improved by 20%. The CRA-PBL integration proved highly effective in addressing fraction addition learning difficulties, achieving complete mastery among target students. This methodology offers a promising framework for inclusive mathematics education, demonstrating that appropriate instructional approaches can overcome traditional learning barriers and enhance educational outcomes for all students.